2013
DOI: 10.1016/j.pt.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Cryptosporidium: the application of advances in detection and diagnosis

Abstract: The protozoan Cryptosporidium is a major public and animal health concern. Young children, immunocompromised people, and pre-weaning animals are especially vulnerable, but treatment options are limited and there is no vaccine. A laboratory diagnosis is required to confirm cases of cryptosporidiosis, and species and genotype determination is essential in distinguishing human from non-human sources, understanding transmission, and strengthening the epidemiological evidence for causative links in outbreaks. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 85 publications
(111 reference statements)
4
124
0
9
Order By: Relevance
“…The diagnostic sensitivity and specificity of EIAs marketed in the UK have been shown to be similar to those provided by AP microscopy (Chalmers et al, 2011). EIAs have the advantage of being readily automated, enabling higher throughput than microscopy (Chalmers & Katzer, 2013). The availability of EIAs for simultaneous detection of both Cryptosporidium and Giardia has been reported to improve laboratory diagnosis especially of the latter (Ellam et al, 2008).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The diagnostic sensitivity and specificity of EIAs marketed in the UK have been shown to be similar to those provided by AP microscopy (Chalmers et al, 2011). EIAs have the advantage of being readily automated, enabling higher throughput than microscopy (Chalmers & Katzer, 2013). The availability of EIAs for simultaneous detection of both Cryptosporidium and Giardia has been reported to improve laboratory diagnosis especially of the latter (Ellam et al, 2008).…”
Section: Resultsmentioning
confidence: 96%
“…The use of EIAs by nearly one-fifth of laboratories (Table 2) is a recent development; a comprehensive UK-wide audit carried out in 2008 found that EIAs were being used in only five of 200 (2.5 %) laboratories . The choice of diagnostic test depends on the number of specimens being tested, performance in local validation, available equipment and facilities, staff skills and training, time and cost considerations (Chalmers & Katzer, 2013). The diagnostic sensitivity and specificity of EIAs marketed in the UK have been shown to be similar to those provided by AP microscopy (Chalmers et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In order to maintain control over cryptosporidiosis, it is important to establish a specific diagnosis that makes it possible to analyze risk factors, plan interventions and identify outbreaks of the disease (CHALMERS & KATZER, 2013). Among the diagnostic methods available for detecting oocysts in hosts' feces, the fluorescence staining technique using auramine has shown the highest affinity for oocyst walls, and this method has been considered sensitive and rapid (McPHERSON & McQUEEN, 1993;HANSCHEID et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, a caracterização molecular de isolados de diferentes origens (animal, humana e ambiental) tem sido amplamente usada com o intuito de investigar o potencial zoonótico das espécies ou genótipos do protozoário (XIAO;FAYER, 2008). Atualmente, 26 espécies de Cryptosporidium são reconhecidas, sendo nove capazes de infectar humanos (ASSIS et al, 2013;SHARMA et al, 2013;KATZER, 2013), sendo que diversos grupos de subtipos e sub-genótipos de Cryptosporidium têm sido identificados, dos quais os subtipos Cryptosporidium parvum IIa e IId foram identificados como zoonóticos (PLUTZER; KARANIS, 2009;HELMY et al, 2013).…”
Section: Com O Advento Da Síndrome Da Imunodeficiênciaunclassified
“…Os protozoários do gênero Cryptosporidium são parasitos intracelulares obrigatórios, pertencentes ao filo Apicomplexa e capazes de se desenvolver nas microvilosidades das células epiteliais do trato gastrintestinalde hospedeiros vertebrados (XIAO et al, 2004;ALDEYARBI, 2011;KATZER, 2013).…”
Section: Introductionunclassified